The variational iterated method for solving integral equations - Aladhab , Abeer (University of Thi-Qar Journal of Science, 2019)
The main objective of this paper is to study the exact solution and approximate solution type of integral equations, by using the variational iteration method, as well as, giving some illustrative examples of linear and nonlinear equations .We tabulate the exact and approximate results.